Systematic Review: Analysis of the Correlation between Neuropathic Pain and VEGF Level - manacika, I wayan; Priyanto, Bambang; Purnaning, Dyah; Winata, Made Arya; Manginte, Mervin Arifianto; haikal, Zikrul; Taufik, Ahmad; Irmayanto, Tomi; Hadi, Lalu Fauzan; Evianto, Evan; Widiyanto; Fatrahady, Lalu Shaktisila; et al. (Lombok Health And Science Journal, 2022)
Neuropathic pain is caused by a lesion or disease of the somatosensory system, including peripheral fibres (AÎ², AÎ´ and C fibres) and central neurons, and affects 7â€“10% of the general population. Multiple causes of neuropathic pain have been described and its incidence is likely to increase owing to the ageing global population, increased incidence of diabetes mellitus and improved survival from cancer after chemotherapy. Literature search through database PUBMED using the keyword â€œneuropathic painâ€ combined with several terminologies such as: 'vascular endothelial growth factor', and 'VEGF'. We take only randomized control trial with English language. We excluded studies that specifically examined another induceable factor which can also cause neuropathic pain. Twenty four hundred and two hundred sixty seven kinds of literature were found, 53 of which were related to neuropathic pain and VEGF, only 6 included the study criteria. The occurrence of neuropathic pain is closely related to increased levels of VEGF-A bound to its receptor, namely VEGFRs. Increased VEGF-A can occur in both the central and peripheral nervous systems which is influenced by various conditions such as hypoxia, inflammation, leukocyte accumulation, increased blood sugar levels in diabetes mellitus, and malignancy. Stem cell therapy with VEGFA has been developed and can be a therapeutic option in neuropathic pain. Keywords: Neuropathic pain, vascular endothelial growth factor